2003
DOI: 10.1046/j.1523-1739.2003.01623.x
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Traits Predicting Amphibian Population Declines in Central America

Abstract: Atributos Ecológicos Predicen Declinaciones Poblacionales de Anfibios en Centro América Resumen: Las poblaciones de anfibios están declinando en todos los continentes donde ocurren, pero no todas las especies han sido afectadas por igual. Algunas especies han sido extirpadas, otras han declinado pero sobreviven, algunas no han declinado notablemente y otras están aumentando. Si las poblaciones de anfibios en varios sitios fueran afectadas por los mismos factores, las especies sobrevivientes deberían compartir

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
367
7
25

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 362 publications
(434 citation statements)
references
References 51 publications
27
367
7
25
Order By: Relevance
“…Other factors, including clutch size, body size and ecological niche, are also considered important [8][9][10][11]. Although in agreement about the importance of these traits, our results go beyond previous results by highlighting the way multiple extrinsic threats may operate across specific ecological groups.…”
Section: Discussion (A) a Global Perspectivecontrasting
confidence: 52%
See 1 more Smart Citation
“…Other factors, including clutch size, body size and ecological niche, are also considered important [8][9][10][11]. Although in agreement about the importance of these traits, our results go beyond previous results by highlighting the way multiple extrinsic threats may operate across specific ecological groups.…”
Section: Discussion (A) a Global Perspectivecontrasting
confidence: 52%
“…For example, for amphibians (and several other groups) small geographical range size has been consistently identified as the most important predisposing factor to decline [5][6][7]. Other factors, including clutch size, body size and ecological niche, have also been identified as potentially important [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…To fully understand the impacts of Bd on amphibians, it is necessary to examine the interactions between life history patterns and environmental variables (i.e., ambient moisture) that can exacerbate or ameliorate Bd prevalence and intensity (Lips et al 2003). We have shown that Bd infection varies seasonally in crawfish frogs (Lithobates areolatus), a North American ranid with a complex life history (Kinney et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Whenever mass die-offs were observed, population declines were rapid (4-6 months), Ͼ50% of species were extirpated, remaining species persisted at Ϸ20% of normal abundance, and recovery time exceeded 15 y postdecline (8). In most cases where dead and dying frogs were observed and subsequent population declines occurred, Batrachochytrium dendrobatidis, a pathogenic fungus known to kill amphibians, was found to be the cause of death for almost all individuals (8 -9).…”
mentioning
confidence: 99%